Automation of processing of the information by means of agent technologies - Lukyanets, D. (Українські технології, 2006)
Modern web-technologies allow developers to realize the Internet-appendix, possessing flexible, convenient and dynamic interfaces, lifting their level up to traditional appendices and by that providing convenience of work in the Network. But, as before, there is actual a problem of effective access to the information for end users, and in process of growth www it only becomes complicated.
Keywords: Report; HTTP; WWW; Berners-whether; NeXT; CERN